1933 Cal. Stat. 925, An Act to Regulate the Possession or Transportation of any Form of Shell, Cartridge or Bomb Containing or Capable of Emitting Tear Gas and Providing Penalties for Violation Thereof, ch. 337, § 1 - (:unkn) unknown (General Publisher, 1933)
Required every person, firm, or corporation who knowingly posses or transports any form of shell, cartridge, or bomb containing or emitting tear gas is guilty of a public offense. Violators sentenced to state prison not exceeding two year or by fine not exceeding two thousand dollars, or both.
--
Keywords: NON-GUN ARMS